PENGEMBANGAN PEMBELAJARAN HIFZHIL-QUR’AN DENGAN PENILAIAN AUTENTIK SEBAGAI PENGGERAK KARAKTERISTIK SISWA DI LEMBAGA PENDIDIKAN FORMAL - Deprizon Deprizon (Kreatifitas Jurnal Ilmiah Pendidikan Islam, 2021)
Development of Learning Hifzhil-Qur'an, need efforts to develop a learning process that develops Characteristics of students who are Authentic in the Institute of Formal Education. with the aim of forming the personal of the Qur'anic students (the Qur'an walks). The method used in this paper is the framework of writing the results of thought (research library). This writing aims to provide knowledge about the importance of learning Hifzhil-Qur'an, the formation of Qur'anic Character and the process of Learning that is Authentic based on curriculum 13 (K 13). The Qur'an is the Guidance and Warehouse of Science. To realize it needs a qualified educational pattern, because Education is an important component in the journey of human children, because education can bring humans to a civilization that advanced and character. Character education is one thing that should take precedence because the wise people say "people who have knowledge of morals without morals is useless".